Multi‐miRNAs‐Mediated Hepatic Lepr Axis Suppression: A Pparg–Dicer1 Pathway‐Driven Mechanism in Spermatogenesis for the Intergenerational Transmission of Paternal Metabolic Syndrome - Yi Lin; Xiuye Ni; Lin Zhu; Yilong Lin; Cai Peng; Zhao Lei; Yihui Wang; Huan Wang; Xiang You; Juan Li; Heqing Shen; Jie Wei (Advanced Science, 2025)
Abstract Bisphenol A (BPA) is an “environmental obesogen” and this study aims to investigate the intergenerational impacts of BPA‐induced metabolic syndrome (MetS), specifically focusing on unraveling mechanisms. Exposure to BPA induces metabolic disorders in the paternal mice, which are then transmitted to offspring, leading to late‐onset MetS. Mechanistically, BPA upregulates Srebf1, which in turn promotes the Pparg‐dependent transcription of Dicer1 in spermatocytes, increasing the levels of multiple sperm microRNAs (miRNAs). Several of these miRNAs are highly expressed in a synchronized manner in liver of the offspring. miR149‐5p, miR150‐5p, and miR700‐5p target a specific region in the Lepr 3′UTR, termed “SMITE” (“Several MiRNAs Targeting Elements”), to negatively regulate Lepr. These inherited anti‐Lepr miRNAs, also referred to inherited anti‐Lepr miRNAs (IAL‐miRs), modulate hepatic steatosis, and insulin signaling through the Lepr regulatory Igfbp2, Egfr, and Ampk. Furthermore, IAL‐miRs inhibit Ccnd1 not only via binding to “SMITE” but also via Lepr–Igfbp2 axis, which contribute to hepatocyte senescence. These pathological processes interact in a self‐reinforcing cycle, worsening MetS in the paternal BPA‐exposed offspring. The findings reveal mechanism wherein lipid metabolism reprogramming in spermatocytes‐induced perturbations of sperm miRNAs, triggered by BPA, leads to intergenerational inheritance of paternal MetS through suppression of the hepatic Lepr axis in the offspring.